In the Context of Memories the Approaches of the Leader of National Struggle aganist Bolshevism - Demirel, Kenan (Celal ÖNEY, 2017)
A memoir is a type of document that one of the people, especially those who are known, has seen, lived or witnessed during the time they lived, based on observation and information. Memories have an important place in terms of their origin in history science. Memories that contain official correspondence in particular are important sources in this area. Despite these features, however, the person who writes his memory weakens the objectivity of the memories because of prominence in his work. Therefore, if works of this kind which are described in the same period or event are used as a source in history writing, other works in this subject must be examined and compared with memorabilia.In this work, the memories are used as a historical document, and what they think about leaders who lead the National Struggle in Bolshevism, what they do in this matter, whether they are against Bolsheviks or are opposed to them is handled comparatively. A nation that succumbed to World War I and was almost desperately wiped out of the historical scene, how their leaders, who saw Bolsheviks as a savior, changed these thoughts against Bolshevism. The reason for this was researched in this study. The aim is to look into the question of whether the Bolsheviks were a viable regime for Anatolia in the course of the National Struggle. In doing so, although we used recollections as the primary source in our research, we used the writings of this leading writer and other works of art in this subject, as well as the works of the biographies of the life stories of these leaders. The purpose of this is to ensure that we can look at the issue objectively, critically and analytically.

Hatirat
Hatiratlar Baglaminda Milli Mücadele Lider Kadrosunun Bolseviklige Karsi Yaklasimlari